Fluidity on Metallic Eutectic Alloys - Morando, Carina (2015)
Eutectic alloys have a great importance both from academic as technological point of view. For technological applications such casting, welding and joining, these systems offer lower melting point than the pure elements and good fluidity. This property is the distance travelled by the liquid metal until it is stopped by solidification when is forced to flow through a channel of small cross section and is called Fluidity Length (LF).Physical variables associated with the process are: metallostatic pressure, heat extraction rate at the metal-mold interface, overheating of the liquid metal and the physico-chemical properties of metal or alloy (latent heat of fusion, density, viscosity, surface tension and solidification mode). In general, pure metals and alloys of eutectic composition have the highest values of fluidity, whilst intermediate composition alloys with greater solidification range show lesser fluidity lengths. Taking into account that the chemical composition plays a fundamental role in the fluidity length by its relation with the resulting microstructure, the aim of this work is to obtain fluidity values of binary and ternary metallic alloys, with different eutectic morphology, in order to determine the relationship between such morphology and the fluidity length and consequently the influence on binary and ternary proeutectic alloys. Fluidity tests were carried out in a linear fluidity device, using alloys of the AlAgCu system in the Al-rich corner and Lead free Sn based alloys, extensively used for important industrial applications. The samples were characterized using Optical Microscopy (OM), Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Microanalysis (EDAX). Usually, Fluidity Length (LF) depends on solidification mode, latent heat of fusion of the alloy and the fluidity of the phases present in the microstructure.